Social Pressure and Self Esteem towards mental disorders in adolescents of Makassar City - Ansyar, Dian Ihwana; Pawenrusi, Nadya Andi; Putri , Rezky Amelia; Raihana; Ramadhani, Nurul Alfira; Rahma, Nuramalia (Universitas Islam Negeri Alauddin Makassar, 2026)
Adolescent mental health is one of the issue important in health society , especially related disturbance anxiety . pressure social and self-esteem are factor psychosocial factors that play a role in influence adolescent mental health . Research This aim For analyze connection between pressure social and self-esteem with mental disorders in the form of anxiety in adolescents in Makassar City. Research This use design quantitative analytic with cross-sectional approach . Sample study totaling 192 teenagers 17–21 years old selected​ use purposive sampling technique . Data collected use Peer Pressure Scale Questionnaire ( PPSQ) questionnaire for measure pressure social , Rosenberg Self-Esteem Scale for measure self-esteem, as well as the Hamilton Anxiety Rating Scale (HARS) to evaluate level anxiety . Data analysis was carried out in a way univariate and bivariate using the Chi-Square test and Fisher's Exact Test as alternative with level significance p < 0.05. Research result show that part big respondents experience pressure social level moderate (71.9%) and have moderate self-esteem (76.0%). Most of them teenager No experience disturbance anxiety (86.5%), however Still found anxiety light until moderate . There is significant relationship​ between pressure social with disturbance anxiety in adolescents (p = 0.020), as well between self-esteem and disturbance anxiety (p = 0.007). Research conclusion This show that pressure social and self-esteem are related in a way significant with mental disorders in the form of anxiety in adolescents in Makassar City. Therefore that , is necessary effort promotive and preventive which focuses on management pressure social as well as strengthening self-esteem for prevent mental disorders in adolescents .